Optimalisasi Media Pembelajaran Pada Pengenalan Permainan Tradisional Indonesia “VINANES” - Noorlela Marcheta; Aulia Rieqy Firhan; Iwan Sonjaya (Departement of Mathematics Education, 2023)
This study aims to create interactive learning media to optimize the introduction of traditional games called